Analysis of Women’s Empowerment through Circular Economy Training Turning Plastic Waste into Keychain Craft - Shafwa Marine Pasekoenda; Sulaeman Fityan Saputra; Natalie Beth Evangeline Alficorista; Hasyatur Razzaq; Dwi Rahma Atiqilah Rizki; Nafisa Hilmy; Arvin Zebe Padantya; Mahira Shafiananta; Fateka Maulana Armedio Kouya; Annisa Siti Zanuba (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Plastic waste has become one of the most pressing environmental problems in Indonesia, while women’s empowerment at the community level still requires sustainable and productive approaches. This study aims to analyze women’s empowerment through circular economy-based training in transforming plastic waste into keychain handicraft in Rowoboni Village, Banyubiru District, Semarang Regency. This study employed a qualitative descriptive approach through participatory training activities involving 15 women members of the Family Welfare Movement (PKK). Data were collected through observation, in-depth interviews, and documentation, and then analyzed using qualitative descriptive analysis. The findings demonstrated that the program successfully improved participants’ skills, creativity, environmental awareness, and self-confidence. Participants were able to transform plastic waste into handicraft products with aesthetic and economic value, while also identifying potential small-scale business opportunities for further development. The program also strengthened social interaction and collaboration among women within the community. This research contributes to the development of community-based empowerment strategies that support sustainable development and local creative economies. Contribution to Sustainable Development Goals (SDGs):SDG 5: Gender Equality; SDG 8: Decent Work and Economic GrowthSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action